HvJNK, a Hydra member of the c-Jun NH2-terminal kinase gene family, is expressed during nematocyte differentiation - Philippe, Isabelle; Holstein, Thomas W. (Gene expression patterns, 2005)
C-jun NH2-terminal kinases (JNKs) represent a subgroup of mitogen-activated protein kinases (MAPKs). MAPK pathways are important regulators of cell proliferation, apoptosis, and gene expression throughout higher metazoans. We report here the characterization of a highly conserved Hydra JNK orthologue (HvJNK) that exhibits amino acid sequence identity of 61% as compared with human JNK1α. Phylogenetic analysis places HvJNK in a cluster with other metazoan JNKs. HvJNK is expressed in the nematocyte differentiation pathway. Double in situ hybridizations demonstrate overlapping expression with two other genes specifically activated during nematocyte differentiation, HyZic and Nowa, and restrict the phase of HvJNK expression to late proliferating nematoblasts and early differentiating nematocytes. Our results indicate that JNKs might have acted in cell differentiation in simple, pre-bilaterian animals.